Biomechanical properties of the cornea measured by the Ocular Response Analyzer and their association with intraocular pressure and the central corneal curvature - Franco, Sandra (2009)
Background: The aim of this study was to investigate the biomechanical properties of the cornea and their association with intraocular pressure (IOP), central corneal thickness (CCT) and the central corneal radius of curvature (Rc). Methods: Eighty-three eyes were divided into two groups. The biomechanical properties of the cornea were measured in 63 normal eyes and in 20 post-laser in situ keratomileusis (LASIK) eyes. The IOP, corneal hysteresis (CH) and corneal resistance factor (CRF) were measured by the Ocular Response Analyzer (ORA). The Rc and CCT were measured using the corneal topographer Medmont E-300 and the Tomey SP-100 Handy ultrasonic pachymeter. Other parameters measured by the ORA, such as TimeIn and TimeOut, were also studied. Results: A mean corneal hysteresis of 10.8 mmHg and CRF of 10.6 mmHg were recorded for the normal eyes. There was no significant association with central curvature. All parameters measured by the ORA showed a significant correlation with the CCT, except for the corneal-compensated intraocular pressure (IOPcc). Both IOPs measured by the ORA had the same values for the mean CH and CRF. For the post-LASIK eyes, the CH and CRF were lower than in the normal non-operated eyes. The TimeIn and the TimeOut also presented lower values for the post-LASIK eyes, suggesting that additional data can be obtained with the ORA measurements. Conclusions: The results of this study indicate that there is no correlation between the parameters measured with the Ocular Response Analyzer and central corneal radius of curvature. Some of the biomechanical properties of the cornea studied were found to differ in the normal eyes compared to the post-LASIK eyes.